Peran Manajemen Sumber Daya Manusia Islami Dalam Pengelolaan Kelembagaan Pada LAZISMU Kota Medan - Putri Handayani; Alfi Amalia (LPPM Universitas Labuhanbatu, 2026)
This study aims to find out how the implementation, concepts, success factors and the role of human resource management in institutional management at Lazismu Medan City. This research method uses qualitative research methods with field research (field research). This data was obtained from literature studies, interviews and observations. The research results obtained concluded that Lazismu has optimally implemented Islamic human resource management, the implementation of Islamic human resource management is carried out by increasing the potential as well as the Islamicity of employees with the morning breafing program, besides that Lazismu also applies Islamic values by obliging read the Koran and Kultum before starting activities every morning. The role of human resource management is very important and is proven to be able to influence the management of existing human resources. This can be seen from the awards and achievements that are achieved every year. The success factor is the result of good cooperation within the organization, because the existence of human resource management is to manage employees in the workplace so that they can achieve the organization's mission and strengthen the work culture in the institution effectively.